Comparison of Early Efficacy of the Percutaneous Presuture Technique with the Femoral Artery Incision Technique in Endovascular Aortic Repair under Local Anesthesia for Uncomplicated Type B Aortic Dissection - Qingsong Wu; Debin Jiang; Xiaochai Lv; Jiaxin Zhang; Rongda Huang; Zhihuang Qiu; Liangwan Chen (Journal of Interventional Cardiology)
Objective. To compare the efficacy of the percutaneous presuture technique (PPST) and the femoral artery incision technique (FAIT) under local anesthesia in the treatment of endovascular aortic repair (EVAR) for patients with uncomplicated type B aortic dissection (uTBAD). Method. Two hundred and ninety-five patients diagnosed with uTBAD who underwent EVAR under local anesthesia from June 2017 to December 2021 were consecutively and randomly selected for retrospective analysis. The PPST was performed in 178 cases and the FAIT was performed in 117 cases. The clinical characteristics and surgical and postoperative data from the two groups were analyzed. Results. There were no significant differences in clinical characteristics between the two groups (p>0.05). The operative time of the PPST group was significantly shorter than that of the FAIT group (46 (33, 58) versus 72 (67.5, 78.0) minutes, p<0.001), as was the operative approach procedure time (6 (4.5, 9.0) versus 38 (36.5, 43.5) minutes, p<0.001), and length of postoperative hospital stay (5.19 ± 2.26 versus 8.33 ± 3.76 days, p<0.001). There were fewer postoperative approach-related procedural complications in the PPST group than in the FAIT group (2 versus 12, p<0.001); similarly, the average frequency of postoperative wound disinfection was significantly lower in the PPST group (1.08 ± 0.39 versus 3.31 ± 0.91 times, p<0.05). Obesity was identified as an independent risk factor for postoperative approach-related procedural complications (OR, 22.26; 95% CI, 4.74–104.49; p<0.001). Conclusions. The PPST has comparable safety and efficacy to the FAIT in EVAR under local anesthesia. It can shorten the length of hospital stay, reduce operation time, lower the risk of wound-related complications, reduce the frequency of postoperative wound disinfection, and hasten postoperative recovery. It can therefore be used as a first-line surgical technique in EVAR of uTBAD under local anesthesia, especially in obese patients.